2020
DOI: 10.3389/fphar.2020.01270
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Depression by Glucagon-Like Peptide 1 Through the Regulation of Neuroinflammation, Neurotransmitters, Neurogenesis, and Synaptic Function

Abstract: Depression has emerged as a major cause of mortality globally. Many studies have reported risk factors and mechanisms associated with depression, but it is as yet unclear how these findings can be applied to the treatment and prevention of this disorder. The onset and recurrence of depression have been linked to diverse metabolic factors, including hyperglycemia, dyslipidemia, and insulin resistance. Recent studies have suggested that depression is accompanied by memory loss as well as depressive mood. Thus, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 218 publications
0
50
0
Order By: Relevance
“…It is also involved in metabolism and decarboxylation to form γ-aminobutyric acid, an inhibitory neurotransmitter. Disruption of neurotransmitters in the brain causes a variety of diseases, including psychosis, depression, anxiety disorder, epilepsy, and Alzheimer's disease (Duan et al 2020;Kim et al 2020), and excitatory toxicity caused by glutamate is part of an ischemic cascade that has been linked to stroke, amyotrophic lateral sclerosis, and Alzheimer's disease (Amantea and Bagetta 2017). In our study, the concentration of l-glutamic acid was higher in MMD patients than in HCs.…”
Section: Discussionmentioning
confidence: 42%
“…It is also involved in metabolism and decarboxylation to form γ-aminobutyric acid, an inhibitory neurotransmitter. Disruption of neurotransmitters in the brain causes a variety of diseases, including psychosis, depression, anxiety disorder, epilepsy, and Alzheimer's disease (Duan et al 2020;Kim et al 2020), and excitatory toxicity caused by glutamate is part of an ischemic cascade that has been linked to stroke, amyotrophic lateral sclerosis, and Alzheimer's disease (Amantea and Bagetta 2017). In our study, the concentration of l-glutamic acid was higher in MMD patients than in HCs.…”
Section: Discussionmentioning
confidence: 42%
“…Consistent with previous studies, in our present work, we found that the levels of leucine and valine were decreased in the brain tissues of the CORT group, while ACE treatment significantly reversed these effects. Moreover, tyrosine, as an aromatic amino acid, is a precursor for the synthesis of catecholamine neurotransmitters ( 51 , 52 ). It was reported that tyrosine was essential in neurotransmitters synthesis under the catalysis of tyrosine hydroxylase ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence is pointing toward an effect of GLP-1 on improving memory and cognition, and GLP-1R agonists are being investigated for the treatment of neurodegenerative disorders. Some of the neuroprotective effects are mediated by increasing neurogenesis and synaptic plasticity (reviewed by Kim et al, 2020 ). This opens an intriguing possibility that one beneficial effect that GLP-1R agonists could play in treating addiction is to open new windows of learning through neuroplasticity.…”
Section: Appetite-regulatory Peptides In Substance Use Disordermentioning
confidence: 99%